Some basic challenges and strategies in teaching translation to Chemistry majors - Elena E. Aksenova; Svetlana N. Orlova (Peoples' Friendship University of Russia (RUDN University), 2018)
Efficient teaching of English for Specific Purposes (ESP) requires substantial effort which includes fostering the skills of scientific texts translation. The study deals with the methodology of teaching translation to MA and post-graduate students specialising in Chemistry and possessing little or no knowledge of translation techniques, reviews discussions on translation theory and practice to illustrate their evolution and attempts to make a contribution to this discussion by offering some new perspectives of interest in the field. The study lists translation strategies to be applied with non-language majors and tests them out with MA and post-graduate students in the Chemistry Department of Moscow Technical University with experiment and control groups further evaluating students' progress via quantitative and qualitative methods of analysis.